Review an update of cetacean ship strikes in the Canary islands - Arbelo Hernández, Manuel Antonio; Arregui Gil, Marina; Bernaldo de Quirós Miranda, Yara; Díaz-Delgado, Josué; Sierra Pulpillo, Eva María; Castro Alonso, Ayoze; De la Fuente, Jesús; Suárez-Santana, Cristian; Fiorito, C.; Fernández Rodríguez, Antonio J. (Servicio de Publicaciones y Difusión Científica de la Universidad de Las Palmas de Gran Canaria (ULPGC), 2023)
The Canary Islands is an archipelago composed of seven main volcanic islands, located in the northwest of Africa. It is one of the richest areas for cetacean biodiversity in the Northeast Atlantic, with 30 species identified. Strikes between vessels and cetaceans have become an issue of concern in the last decades due to an increase of the number and speed of ships. Areas with high cetacean diversity and high maritime traffic overlap have been identified as hot spots as ship strikes may compromise the population status of some cetacean species in those areas. In Europe, these areas include the Ligurian Sea, the Helenic Trench and the Balearic Islands in the Mediterranean Sea, the Strait of Gibraltar, and the Canary Islands. International but mainly inter-island ferry traffic in the Canarian waters has increased considerably in the last years including normal ferries, fast ferries, and high-speed ferries. The review and update of the Canary Islands Cetacean Stranding Network data, shows that ship collisions have affected a total of 81 cetaceans belonging to 12 species in the last 24 years (8 mysticetes: 3 fin whales, 3 Bryde´s whales, 1 sei whales and 1 humpback whale; and 73 odontocetes: 5 short-finned pilot whales, 9 pigmy sperm whales, 10 beaked whales, 47 sperm whales and 2 small delphinids), 38 of these cases were confirmed by forensic studies. The average per year of ship strikes in this period (1999-2022) is 3.48 for all the species, and 2,02 for sperm whales. These data and the increasing numbers of highspeed ferries and routes, raises concern about the impact of ship strikes in the conservation of cetaceans, mainly sperm whales in the Canary Islands. 210 209 2